Prenatal Detection and Postnatal Outcome of Persistent Left Superior Vena Cava and Agenesis of Ductus Venosus Associated with Postnatal Bovine Aortic Arch - Elbistanli, Ceylin; Yozgat, Yılmaz; Dogan, Mehmet Said; Yozgat, Can Yilmaz; Kütük, Mehmet Serdar (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Background Isolated agenesis of ductus venosus (ADV) is usually a benign condition, but it may be associated with cardiovascular defects, hydrops, growth restriction, and chromosomal abnormalities. Additionally, persistent left superior vena cava (PLSVC) and bovine aortic arch are relatively common fetal anomalies. To the author’s knowledge, this is the first report of prenatal detection of DV agenesis and PLSVC associated with the postnatal bovine aortic arch with a hypoplastic transverse aortic arch.Case A 25-year-old, G2P1 woman was referred to our department at 31 weeks due to fetal growth restriction and short femur. On fetal echocardiography, DV could not be viewed via two-dimensional (2D) and Doppler ultrasound (US) imaging; there was also evidence of the co-occurrence of PLSVC and an aortic arch anomaly. We revealed the intrahepatic continuation of the umbilical vein. A weekly follow-up program was scheduled for the patient and the rest of the pregnancy was uneventful. Postnatal, thorax computer tomography and transthoracic echocardiography (TTE) demonstrated PLSVC and bovine aortic arch associated with hypoplastic transverse aortic arch. Routine echocardiographic examinations revealed that the blood flow of the aortic arch had increased gradually, and the male infant’s aortic arch had significantly widened and reached the normal range until the baby was discharged from the hospital.Conclusion DV agenesis and PLSVC are usually benign conditions but underlying serious heart diseases may accompany them. Therefore, in situations like ours, a prenatal aortic arch evaluation is of capital importance. Postnatal hemodynamic changes should be taken into consideration in the management of these cases. This is the first example in the literature that these abnormalities co-existed in one case.
Keywords: Ductus Venosus Agenesis; Transverse Arch Hypoplasia; Bovine Aortic Arch; Fetal Echocardiography